2012
DOI: 10.2478/v10078-012-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Depth on Drag During the Streamlined Glide: A Three-Dimensional CFD Analysis

Abstract: The aim of this study was to analyze the effects of depth on drag during the streamlined glide in swimming using Computational Fluid Dynamics. The Computation Fluid Dynamic analysis consisted of using a three-dimensional mesh of cells that simulates the flow around the considered domain. We used the K-epsilon turbulent model implemented in the commercial code Fluent® and applied it to the flow around a three-dimensional model of an Olympic swimmer. The swimmer was modeled as if he were gliding underwater in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…The significance of optimal finger spreading can be roughly quantified in terms of swimming time. A swimmer can reach a speed of v s = 2 m/s in front crawl swimming and experiences a drag force of F D = 100 N [25,33,29,16]. Assume that the stroke frequency of a complete cycle is 0.5 s −1 (propulsive phase of one arm takes 1 s) and the backward (slip) velocity of the hand with respect to the water is v h = 2.2 m/s [2,20,7,4].…”
Section: Resultsmentioning
confidence: 99%
“…The significance of optimal finger spreading can be roughly quantified in terms of swimming time. A swimmer can reach a speed of v s = 2 m/s in front crawl swimming and experiences a drag force of F D = 100 N [25,33,29,16]. Assume that the stroke frequency of a complete cycle is 0.5 s −1 (propulsive phase of one arm takes 1 s) and the backward (slip) velocity of the hand with respect to the water is v h = 2.2 m/s [2,20,7,4].…”
Section: Resultsmentioning
confidence: 99%
“…By modifying disk orientation and flow characteristics (constant or variable acceleration), they found that hand acceleration (from 2.84 to 5.84 m/s) strongly increased propulsive drag by up to 40%. Following this study, interest turned to evaluating water resistances during glide periods [54,[66][67][68][69]. Investigators scanned the swimmer's whole body and tested resistances as a function of position (arms extended at the front or along the body) and depth.…”
Section: Fluid Perturbations From Swimmer's Movementmentioning
confidence: 99%
“…Investigators scanned the swimmer's whole body and tested resistances as a function of position (arms extended at the front or along the body) and depth. It appeared that passive drag decreased when depth increased: water drag is maximum at 0.25 m depth, and minimal around 0.75 m depth [68]. Thus, it became clear that swimmers' actions induce different fluid behaviours and that therefore fluid behaviours and swimmer actions need to be considered as an interactive dynamical system [7,9,10].…”
Section: Fluid Perturbations From Swimmer's Movementmentioning
confidence: 99%
“…Por otro lado, el nado subacuático también se caracteriza por no tener un desplazamiento rectilíneo y a la misma profundidad durante la fase del deslizamiento y la propulsión subacuática, según la división que hicieron Elipot et al (2010b Novais et al (2012) contrastaron dichas afirmaciones, ya que en su estudio la velocidad inicial tras el impulso y la resistencia hidrodinámica podrían condicionar el rendimiento del deslizamiento y de la fase subacuática. Por consiguiente, si el nadador consiguiese minimizar tal resistencia, posiblemente mejorarían los resultados que el simple hecho de aumentar el esfuerzo durante el impulso no incrementando el coste metabólico (Lyttle et al, 1998).…”
Section: Caracteristicas De La Fase Subacuática De Nadounclassified
“…Aun así, hay autores que también señalan que una inadecuada profundidad o mala trayectoria (Vennell, Pease y Wilson, 2006;Novais et al, 2012) tras la entrada en el agua después de la salida o un mal impulso después de la trayectoria del viraje, podrían incrementar la resistencia y ralentizando al nadador (Blanksby, Gathercole y Marshall, 1996;Lyttle et al, 1998;Lyttle y Benjanuvatra, 2005;Sanders y ByattSmith, 2001), acortando así la distancia del deslizamiento.…”
Section: Tiempo Del Deslizamiento Subacuáticounclassified